TRANSFORMASI DIGITAL DAN BRANDING KREATIF PRODUK OPAK GULUNG UNTUK MENINGKATKAN DAYA SAING UMKM DI DESA PASEBAN - Titin Nurhidayati; M Nafiur Rofiq; Eka Harlin Susiani; Nur Azizah; Yakub Hamdani Ali; Noval Firmansyah; M Syaivan Hidayat; Diva Asadia Nirmala Nugraha; Muhammad Rizzal Pahrefi; Lukmatun Naimah; Rafida Tri Nurhidayah; Ferdy Eka Permaisugi; Husnul Hotimah; Fitria Ramadanti (Universitas Al-Falah As-Sunniyah Kencong Jember, 2026)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in driving the local economy, including in Paseban Village, Jember, which is known for its ‘Opak Gulung’ product a traditional food based on local wisdom. However, limited use of digital technology and weak branding strategies hinder the competitiveness of these products in wider markets. This Community Service Programme aims to enhance the capacity of 40 MSME operators through digital awareness-raising and creative branding training. The implementation method employs the Asset-Based Community Development (ABCD) approach. The results of the activities show an 83.3% increase in partners’ conceptual understanding, with the average score rising from 48.00 to 88.00. In terms of technical skills, there was a 95.4% improvement in content design capabilities. Furthermore, there was a 100% increase in the adoption of digital platforms, with partners now managing an average of two independent marketing platforms. This demonstrates that integrating digital marketing and creative branding effectively enhances the competitiveness of Opak Gulung SMEs in Paseban Village towards economic self-reliance.